Politik Hukum Pidana dalam Pencegahan dan Pemberantasan Judi Online di Indonesia - Sri Nur Damayana; Muh Anugrah Kurniawan Amir (Eksekusi : Jurnal Ilmu Hukum dan Administrasi Negara, 2024)
Digital technology not only makes it easier to access information, but also creates new opportunities in various fields, such as economics, education and entertainment. However, on the other hand, this progress also opens up opportunities for illegal practices that utilize digital platforms, one of which is online gambling. This research aims to analyze criminal law regulations in Indonesia governing the prevention and eradication of online gambling and the politics of criminal law can be strengthened to increase the effectiveness of law enforcement against online gambling in Indonesia. This research is a type of normative research. The approach used is a statutory approach. and conceptual approaches. The research results show that criminal law regulations in Indonesia have provided a strong basis for cracking down on online gambling, but technological challenges make implementation difficult. Strengthening criminal law politics through regulatory reform, increasing apparatus capacity, and synergy between institutions is needed to effectively eradicate online gambling and maintain societal stability.